Improvement of methane production from P. canaliculata through mechanical pretreatment. (April 2018) - Rodriguez, C.; Alaswad, A.; El-Hassan, Z.; Olabi, A.G.
Abstract: In order to increase the methane yield from biomass, this paper investigates the mechanical pretreatment effect of a Hollander beater on the anaerobic digestion process of Pelvetia canaliculata macroalgae using a response surface methodology (RSM). Higher values on methane yield were obtained at lower F/I ratios, with an increase up to 2.5-fold at an F/I value of 0.3. A multi-objective optimization study was carried out with the aim of maximizing the methane yield while minimizing the pretreatment time. An optimum methane yield of 283 ml/gVS was obtained for 50 min pretreatment time and a ratio F/I of 0.3, which represents an increase of 45% compared to non-pretreated algae. Highlights: Response surface methodology (RSM) with a Composite Central Design (CCD) was applied. The highest methane yields were achieved at feedstock/inoculum ratio 0.3. An optimized methane yield of 283 ml/gVS was achieved for 50 min pretreatment.